Hazard assessment studies on hydrocarbon fire and blast: An overview - Imran, M. (American Scientific Publishers, 2017)
Fire is always a greater threat to offshore platform due to the presence of hydrocarbon gases. The temperature of hydrocarbon fire can exceed 1000 °C in less than 10 minutes which cause severe damages to the structure. The average body can get 3rd degree burn immediately as exposed to 72 °C. Past accidents like Piper Alpha and Deep-water Horizon and many others were caused by uncontrolled hydrocarbon fire and blast. The hazard assessment studies such as qualitative and quantitative risk analysis, scenario-based studies started after major planning of the facilities, which make mitigation costly. These studies are not only complex, costly, time consuming but also required high-quality historical data. The scenarios selections are usually based on expert’s opinion, history of past accidents and safety reviews. Neglecting any potential scenario can cause heavy life and property losses. The impact of hydrocarbon fire and blast can escalated instantly due to wrong prediction and causes chain of uncontrolled events. Only a few studies focused on modeling and validation of structural member under fire. Therefore, the purpose of this overview is to highlight the details of personal hazard and hazard assessment techniques for fire and blast for offshore platform and to reduce property and lives losses. © 2017 American Scientific Publishers All rights reserved.